Renovating the Canadian Old Age Home: The Evolution of Residential Care Facilities in B.C., 1930-1960 - Davies, Megan (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2001)
AbstractCanadian historians have largely ignored the old age home. Focussing on British Columbia, this paper covers a pivotal period of institutional transformation from the 1930s through to the 1950s, when health and social welfare professionals sought to reshape the old age home from a custodial poor law facility to a middle-class medical “home” inhabited by deserving senior citizens. New names, architectural styles, décor, and professional involvement within the institution were meant to reform residential accommodation for Canada's elderly. However, professionals' ageism, divisions created by class and gender, and an increasingly frail institutional population made this process problematic.